Pemanfaatan Kelompok Sosial dalam Perlindungan Anak di Kabupaten Maros - Muh. Iqbal Latief; Ridwan Syam; Sultan; Hariashari Rahim; Andi Nurlela (CV. Literasi Indonesia, 2022)
Maros Regency, South Sulawesi Province (South Sulawesi), already has a Regional Regulation (Perda) on Child Worthy Districts. However, the implementation of this policy is still low because there are still several cases regarding violence and immoral acts against children. Macro-wise, this is also in line with the publication of the Child Protection Commission in 2020. There were 4734 cases of child complaints. This is because the implementation of the Child Protection Law Number 35 of 2014 is still lacking in terms of mentoring children. Therefore, a social institutional approach is needed to bridge between regulation and various child protection issues. This study focuses on using social groups in child protection in Maros. The method used is participatory discussion. The results of this service illustrate that, although the Maros Regional Government already has a tiered planning mechanism in the form of a Development Planning Deliberation starting from the village level as material for compiling a child protection program for Maros Regency as a whole. However, it seems less than optimal, because the government does not have sufficient ability to play its role as a catalyst for development. For this reason, further efforts are needed to increase the use of social groups in child protection in Kabupaten Maros. The social group serves as a channel to solve various problems related to child protection in Maros County. Therefore, existing social groups are empowered in the form of institutional strengthening and capacity building of available resources so that the quality of protection and welfare of children in the Maros Regency can be achieved.